Changes in the Characteristics of After Logging Streamflow Hydrograph of Eucalyptus pellita F. Muell Stands - Agung Budi Supangat (Jurnal Penelitian Kehutanan Wallacea, 2017)
Eucalyptus pellita F. Muell plantation in Riau Province applying the clear cutting silvicultural system on fast growing tree species allegedly have an impact on the changing of watershed hydrological functions. The aim of this study was to determine the changes in the chara cteristics of after logging stream flow hydrograph of E. pellita forest stand. The research was carried out in E. pellita plantations in Perawang, Riau Province using 4.62 ha of micro catchment as an observation unit. The method used is the analysis of hyd rograph units on chosen data of flood hydrograph. The research concludes that clear cutting system has led to increasing the peak flow discharge from an average of 0.226 m 3 .s 1 to be 0.322 m 3 .s 1 , shortening the time base of hydrograph from an average of 1 43 minutes to be 90 minutes, shortening the time to peak flow from an average of 80 minutes to be 40 minutes, as well as declining the base flow from an average of 0.0056 m 3 .s 1 to be 0.0032 m 3 .s 13.s-1to be 0.0032 m3.s-1.